Synthesis and Preliminary Anticancer Evaluation of 6-Mercaptopurine -Methotrexate Conjugate as Possible Mutual Prodrug - Asmaa S. Al-Darraji; Mohamed H.Mohamed (College of Pharmacy University of Baghdad, 2019)
Small molecules drug conjugate mutual prodrug design  (SMDC) composed of folate and lethal agent conjugate, rigidly bonded via hydrophilic bridge and self immolative disulfide  bond   ;  represent new interesting approaches for cancer treatment , the component of SMDC intended  for targeting    folate receptor , along with greater conservation  of component until reaching  the target tumor tissue . The  designing and synthesis of compound VI and VIII derived from 6-Mercaptopurine (6-MP) and Methotrexate ( MTX) conjugate altogether as mutual prodrugs were  processed forward  successfully by multistep reaction  procedures , and by Thin Layer Chromatography (TLC) for  preliminary detection of  products and their intermediates, along with their purity. The structures of two final compounds and their intermediates were proclaimed by melting point measurement, infrared spectrometry and ¹HNMR analysis given results greatly correspond with theoretical proposed chemical structure of synthesized compounds. Furthermore, cytotoxic activity evaluation on cell line level had been done for two final compounds against human breast tumor cell (MCF-7) and human ovarian tumor cell (SKO-3) types of cancer cell line and the results were confirmed which show greater cytotoxic tumor activity of two final compounds, while compound VI   possess optimal activity proportional with increased number of 6-MP molecules.